Iron Age Terracotta Figurines from the Southern Levant in Context - Erin D. Darby; Izaak J. de Hulster (Les Carnets de l’ACoSt)
The volume deals with the iconography, typology, and find context of female, male, animal, and furniture figurines and discusses their production, appearance, and provenance, including their identification and religious functions.